Trauma-informed care in the UK: where are we? A qualitative study of health policies and professional perspectives - Elizabeth Emsley; Joshua Smith; David Martin; Natalia V. Lewis (BMC, 2022)
Abstract Background Trauma-informed (TI) approach is a framework for a system change intervention that transforms the organizational culture and practices to address the high prevalence and impact of trauma on patients and healthcare professionals, and prevents re-traumatization in healthcare services. Review of TI approaches in primary and community mental healthcare identified limited evidence for its effectiveness in the UK, however it is endorsed in various policies. This study aimed to investigate the UK-specific context through exploring how TI approaches are represented in health policies, and how they are understood and implemented by policy makers and healthcare professionals. Methods A qualitative study comprising of a document analysis of UK health policies followed by semi-structured interviews with key informants with direct experience of developing and implementing TI approaches. We used the Ready Extract Analyse Distil (READ) approach to guide policy document review, and the framework method to analyse data. Results We analysed 24 documents and interviewed 11 professionals from healthcare organizations and local authorities. TI approach was included in national, regional and local policies, however, there was no UK- or NHS-wide strategy or legislation, nor funding commitment. Although documents and interviews provided differing interpretations of TI care, they were aligned in describing the integration of TI principles at the system level, contextual tailoring to each organization, and addressing varied challenges within health systems. TI care in the UK has had piecemeal implementation, with a nation-wide strategy and leadership visible in Scotland and Wales and more disjointed implementation in England. Professionals wanted enhanced coordination between organizations and regions. We identified factors affecting implementation of TI approaches at the level of organization (leadership, service user involvement, organizational culture, resource allocation, competing priorities) and wider context (government support, funding). Professionals had conflicting views on the future of TI approaches, however all agreed that government backing is essential for implementing policies into practice. Conclusions A coordinated, more centralized strategy and provision for TI healthcare, increased funding for evaluation, and education through professional networks about evidence-based TI health systems can contribute towards evidence-informed policies and implementation of TI approaches in the UK.